Translocalising and Relocalising Antifascist Struggles: From #KämpaShowan to #KämpaMalmö. Issue 1 (28th October 2018) - Merrill, Samuel; Pries, Johan
Abstract: This article explores the translocal hybrid activism surrounding two demonstrations triggered by a violent altercation between antifascists and neo‐Nazis in Malmö in March 2014. It maps the appearance and spread of the hashtag that underpinned this activism: #KämpaShowan. It also considers how the hashtag was articulated, adopted and adapted by different activists in ways that led to the emergence of a new hashtag: #KämpaMalmö. It shows how the action frames foregrounded by #KämpaShowan stimulated its translocal diffusion but were also criticised by local activists who in turn tried to relocalise the energy behind the hashtag and shift its associated action frames. The article thus reveals how antifascist activists might respond to far‐right violence with social media tactics that attract broader publics and break the isolation often caused by more confrontational street politics. It also highlights how these tactics can stretch across geographical scales involving processes of relocalisation as much as translocalisation.